Evaluation of Antidepressant Effect of Ethanolic and Aqueous Extracts of Silybum marianum L. Seed in Mice - Gh Karimi; M Saradeghi Keisari (Institue of Medicinal Plants, ACECR, 2007)
Background: Depression is one of the most psychiatric disorders that there are many treatments for it. Milk thistle is a plant which has many pharmacologic effects such as antioxidant, anti-inflammatory and anticancer. It is reported that silymarin (main component of milk thistle) increase the concentration of some neurotransmitter in brain. Objective: Evaluation of the antidepressant effect of aqueous and ethanolic extracts of milk thistle. Methods: We investigated the antidepressant effect of aqueous (0.72, 1.26, 1.80 g/kg) and ethanolic (0.24, 0.42, 0.6 g/kg) extracts using modified forced swimming test in mice. Results: The ethanolic extract did not have any effect on the duration of immobility of mice. However, the aqueous extract significantly reduced the duration of immobility versus the control group. Conclusion: Aqueous extract of milk thistle showed antidepressant effect in animal model.